Studi penurunan suhu palka dan ikan hasil tangkapan - Yulvin Kala'Tiku; Frangky E. Kaparang; Vivanda O. J. Modaso (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2023)
This study aimed to examine the handling of the caught fish using a purse seine on KMN Magfira 04 ship operated in the Makassar Strait. The observations were carried out for four trips on the process of catching and catch handling after fishing till unloading at fishing port. This research was carried based on a descriptive case study.  The main data were collected through direct observation and interviews with the ship crews and the captain, while the supporting data were collected through a literature study. The data including  ice temperature, fish hold room temperature, outside room temperature and the temperature of dominant catch species were analysed descriptively and numerically using Microsoft Excel. The temperature of the hold containing the coldest fish in trip III and trip IV reached 0,2 oC after 48 hours. This was due to the replacement of the hatch lining with new styrofoam and plastic tarpaulin covering the leaky hatch lining before sailing on trip III. The largest decrease in fish body temperature during the four trips was found on mackerel (24,75 oC); then flying fish (24,02 oC); tuna (23,35 oC) and skipjack tuna (22,56 oC).